1
$\begingroup$

I have encountered these two gradients $\triangledown_{w} w^{t}X^{t}y$ and $\triangledown_{w} w^t X^tXw$, where $w$ is a $n\times 1 $ vector, $X$ is a $m\times n$ matrix and $y$ is $m\times 1$ vector.

My approach for $\triangledown_{w} w^{t}X^{t}y$ was this:

$w^{t}X^{t}y$ =

$= y_1(\sum_{i=1}^{n}w_ix_{1i}) + y_2(\sum_{i=1}^{n}w_ix_{2i}) + ... + y_m(\sum_{i=1}^{n}w_ix_{mi})$ $= \sum_{j=1}^{m}\sum_{i=1}^{n} y_jw_ix_{ji}$

And I'm stuck there, not knowing how to convert it to matrix notation. I'm not even sure if it is correct.

How can I get the actual gradient $\triangledown_{w} w^{t}X^{t}y$ out of that partial derivative? Is there an easier way to get the gradient (maybe using some rules, like in ordinary calculus), because this way using summation seems tedious, especially when you have to calculate $\triangledown_{w} w^t X^tXw$?

How do I then work out $\triangledown_{w} w^t X^tXw$ ?

$\endgroup$
  • $\begingroup$ Your derivation is correct. It's simple to convert this result back into matrix notation $$\sum_j X_{ja}y_j=X^Ty$$ it just takes a little bit of practice. Now try the second one, just remember to handle the 2 $w$'s seperately. $\endgroup$ – greg Jan 6 '18 at 15:55
2
$\begingroup$

Let

$$f (\mathrm x) := \rm x^\top A \, x$$

Hence,

$$f (\mathrm x + h \mathrm v) = (\mathrm x + h \mathrm v)^\top \mathrm A \, (\mathrm x + h \mathrm v) = f (\mathrm x) + h \, \mathrm v^\top \mathrm A \,\mathrm x + h \, \mathrm x^\top \mathrm A \,\mathrm v + h^2 \, \mathrm v^\top \mathrm A \,\mathrm v$$

Thus, the directional derivative of $f$ in the direction of $\rm v$ at $\rm x$ is

$$\lim_{h \to 0} \frac{f (\mathrm x + h \mathrm v) - f (\mathrm x)}{h} = \mathrm v^\top \mathrm A \,\mathrm x + \mathrm x^\top \mathrm A \,\mathrm v = \langle \mathrm v , \mathrm A \,\mathrm x \rangle + \langle \mathrm A^\top \mathrm x , \mathrm v \rangle = \langle \mathrm v , \color{blue}{\left(\mathrm A + \mathrm A^\top\right) \,\mathrm x} \rangle$$

Lastly, the gradient of $f$ with respect to $\rm x$ is

$$\nabla_{\mathrm x} \, f (\mathrm x) = \color{blue}{\left(\mathrm A + \mathrm A^\top\right) \,\mathrm x}$$

$\endgroup$
  • $\begingroup$ Thank you Rodrigo! Even though you didn't answer my question directly, you provided me with a method to evaluate gradients that I was able to use and compute them correctly. Is this method going to work generally on any kind of matrix-vector expression? Furthermore, why is it that you have to express it in a form of inner product like ⟨v, *some expression*⟩ to get the actual gradient? $\endgroup$ – user3071028 Jan 6 '18 at 16:07
  • $\begingroup$ This works for functions that take matrices or vectors and produce scalars. Using the Taylor expansion, $$\lim_{h \to 0} \frac{f (\mathrm x + h \mathrm v) - f (\mathrm x)}{h} = \langle \mathrm v , \nabla_{\mathrm x} \, f (\mathrm x) \rangle$$ $\endgroup$ – Rodrigo de Azevedo Jan 6 '18 at 16:12
  • $\begingroup$ Oh, I see, thank you! Is there a similar way to get the derivative of a vector-valued or a matrix-valued function? $\endgroup$ – user3071028 Jan 6 '18 at 16:35
  • $\begingroup$ Take a look at these. $\endgroup$ – Rodrigo de Azevedo Jan 6 '18 at 16:47
  • $\begingroup$ I will, thank you so much man! $\endgroup$ – user3071028 Jan 6 '18 at 17:02
1
$\begingroup$

By the definition of what is to be the gradient vector of the application $$ \mathbb{R}^{n\times 1}\ni w \mapsto w^tX^ty= \sum_{i=1}^n\sum_{j=1}^m w_{i1}\cdot X_{ji}\cdot y_{1j}\in\mathbb{R} $$ we have $$ \nabla_w \big( w^tX^ty \big) = \left( \frac{\partial}{\partial w_{11}} ( w^tX^ty ), \frac{\partial}{\partial w_{21}} ( w^tX^ty ), \ldots, \frac{\partial}{\partial w_{i1}} ( w^tX^ty ), \ldots, \frac{\partial}{\partial w_{21}}( w^tX^ty ), \right) $$ For $i_0=1,2,\ldots,n$; \begin{align} \frac{\partial}{\partial w_{i_0}} ( w^tX^ty ) =& \frac{\partial}{\partial w_{i_01}} \left( \sum_{i=1}^n\sum_{j=1}^m w_{i1}\cdot X_{ji}\cdot y_{1j} \right) \\ =& \sum_{i=1}^n\sum_{j=1}^m \frac{\partial}{\partial w_{i_01}} (w_{i1}\cdot X_{ji}\cdot y_{1j}) \\ =& \sum_{j=1}^m \frac{\partial}{\partial w_{i_01}} (w_{i_01}\cdot X_{ji_0}\cdot y_{1j}) \\ =& \sum_{j=1}^m X_{ji_0}\cdot y_{1j} \\ \end{align} Then $$ \nabla_w \big( w^tX^ty \big) = \left( \sum_{j=1}^m X_{j1}\cdot y_{1j}, \sum_{j=1}^m X_{j2}\cdot y_{1j}, \ldots, \sum_{j=1}^m X_{ji_0}\cdot y_{1j}, \ldots, \sum_{j=1}^m X_{jn}\cdot y_{1j}, \right) $$ With similar calculations, we get the gradient vector of the application $$ \mathbb{R}^{n\times 1}\ni w \mapsto w^tX^tXw= \sum_{1\leq k\leq m} w_{1k}^2\cdot X_{k k}^2 + 2\sum_{1\leq k<\ell \leq m} w_{1k}\cdot X_{\ell k}\cdot X_{k\ell}\cdot w_{1\ell} \in\mathbb{R}. $$

$\endgroup$
0
$\begingroup$

Better use $w^tX^ty=(w^tX^ty)^t=y^tXw$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.